2010
DOI: 10.1099/ijs.0.011049-0
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia hoogstraalii sp. nov., isolated from hard- and soft-bodied ticks

Abstract: A novel spotted fever group Rickettsia was found in Haemaphysalis sulcata ticks collected from sheep and goats in Croatia in 2006. At the same time, a genetically identical organism was coisolated with the embryonic cell line CCE3 obtained from the soft tick Carios capensis in Georgia, USA. In this study, further phenotypic and genotypic characteristics of the novel rickettsial strain present in H. sulcata ticks were investigated. Based on the cultivation of bacteria in mosquito and Vero cell cultures, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 15 publications
1
40
0
2
Order By: Relevance
“…R. hoogstraalii has been originally detected in H. sulcata from sheep and goats in Croatia, and it is closely related to Rickettsia felis [12]. Duh et al [13] showed that it causes a cytopathic effect in Vero cells and different arthropod cell lines, but its pathogenicity in vertebrate hosts is unknown. Other reports from Europe refer to infection in Haemaphysalis spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R. hoogstraalii has been originally detected in H. sulcata from sheep and goats in Croatia, and it is closely related to Rickettsia felis [12]. Duh et al [13] showed that it causes a cytopathic effect in Vero cells and different arthropod cell lines, but its pathogenicity in vertebrate hosts is unknown. Other reports from Europe refer to infection in Haemaphysalis spp.…”
Section: Discussionmentioning
confidence: 99%
“…Our gltA sequences, from both I. ricinus and H. sulcata (GenBank Accession No. KY418024, KY418025), showed 100% similarity to the Rickettsia endosymbiont of H. punctata isolate Hae69 from Spain (EU303311) and 99% to the endosymbiont of H. sulcata from Croatia (DQ081187); these endosymbionts have been subsequently classified as R. hoogstraalii by Duh et al [13]. The OmpB gene (GenBank Accession No.…”
Section: Infection By Tbd Agents In Ticks and Tissues From Lizardsmentioning
confidence: 99%
“…In addition, the existence of another novel SFG rickettsiae was demonstrated in Haemaphysalis sulcata ticks collected from sheep and goats in Croatia. This new rickettsia was named R. hoogstraali, and was isolated and deposited in two different collections (Duh et al, 2009). A rickettsial genotype from the R. massiliae genogroup called Candidatus Rickettsia kulagini was identified in Rh.…”
Section: Other Tick-borne Rickettsiaementioning
confidence: 99%
“…Currently, 26 Rickettsia species with validated and published names have been reported (http://www.bacterio.cict.fr/qr /rickettsia.html), including Rickettsia asiatica (3), Rickettsia heilongjiangensis (4), Rickettsia hoogstraalii (5), Rickettsia raoultii (6), and Rickettsia tamurae (7), which were reported since 2005 (2). In addition to these 26 species, subspecies have been proposed within the Rickettsia conorii (8) and Rickettsia sibirica (9) species.…”
Section: Taxonomic and Genomic Bacteriology: The Revolutionmentioning
confidence: 99%
“…In the last 7 years, two Rickettsia species within the SFG were isolated: Rickettsia hoogstraalii from Haemaphysalis sulcata ticks collected from sheep and goats in Croatia, which are closely related to R. felis (5), and Rickettsia genotype AvBAT from Argas vespertilionis, soft bat ticks, collected from southern France (318). In addition, R. hoogstraalii was detected in 30% of the Haemaphysalis punctata ticks collected in Cyprus (258) and in 3% of H. punctata and 16% of H. sulcata ticks from Spain (319).…”
Section: Species Of Unknown Pathogenicitymentioning
confidence: 99%